A cross sectional study on the prevalence, knowledge, attitude and practice of hypercholesterolaemia among the sampled population of age 35 years and above in kampung Sadong Jaya from 14th June to 20th August 2004 - Zuffazarina, binti Zulkapli; Thanuja, a/p Mahaletchumy; Shazni Izana, Binti Shahruddin; Peter, ak Jerampang; Ming, Koe Hooi; Daphne Dewi, ak Stephen Kalong; Seng, Alex Lee Fook; Aisah Munirah, binti Wahi; Norizan, binti Rosli; Noor Suhaila, binti Abu Bakar; Mursyida, binti Md Nujid; Mariza, binti Md Rasip; et al. (Universiti Malaysia Sarawak (UNIMAS), 2004)
Hypercholesterolaemia is a disease condition, which is on the rise worldwide, owing mainly due to the changes in lifestyle and dietary habits. It is a condition where there is excess cholesterol in the blood. It is one of the major risk factors for cardiovascular mortality. Although hypercholesterolaemia is normally thought as a `disease among the urban', but since Malaysia is progressively encroaching modernization, the effect of urbanization, especially regarding health, will leak towards it's surrounding area, including the rural parts. A cross-sectional study on the prevalence, knowledge, attitude and practice of hypercholesterolaemia among the sampled population aged 35 years old and above was carried out in Kampung Sadong Jaya. Through census and EPI info 6.04 a total of 150 respondents were randomly selected for questionnaire interviews, measurements of total cholesterol level and body mass index. The exclusion criteria include those who are severely ill, and those that refuses even after 3 attempts of approaching the respondent fails. From the research that has been conducted, only about half of the respondents, which accounts towards 55.0%, had good knowledge regarding Hypercholesterolaemia while another 45.0% did not. Furthermore, there were 60.0% of respondents having good attitude and another 40.0% have unhealthy attitude regarding Hypercholesterolaemia. A percentage of 54.0% respondents have good practice while another 46.0% did not. As for the prevalence of hypercholesterolaemia among the respondents, 69.0% of the respondents had desirable total cholesterol (less than 5.20 mmol/1), 25.0% had borderline hypercholesterolaemia (from 5.21 mmol/l to 6.20 mmol/1) while 6.0 % had high risk of hypercholesterolaemia (more than 6.20 mmol/1).